AKUNTABILITAS PEMERINTAHAN DESA DALAM PENGELOLAAN ANGGARAN PEMBANGUNAN DESA - Ummi Zakiyah; Ginesta Monra Jelis Sihombing; Mohamad Yusran Al Aufar; Nadaa Syafira; Siti Hofifah (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2020)
Abstract, The purpose of this study is to determine the application of the principles of transparency and accountability in the management of APBDes which includes planning, implementation, reporting, and accountability activities. The research method used is a qualitative method with a descriptive approach. The respondents of this study consisted of the village secretary, treasurer of the PKK, and community representatives. Data collection techniques are by interview, observation and documentation. Data analysis techniques began with data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the apparatus of the Pusaka Rakyat Village, Tarumajaya District has applied the principles of transparency and accountability in the management of the APBDes. APBDes planning and implementation has applied the principles of transparency and accountability. While APBDes accountability physically shows an accountable implementation. The main obstacle is the disbursement of funding sources that are not according to plan. Keywords: Accountability, APBDes Abstrak, Tujuan dari penelitian ini adalah untuk menentukan penerapan prinsip-prinsip transparansi dan akuntabilitas dalam pengelolaan APBDes yang mencakup kegiatan perencanaan, pelaksanaan, pelaporan, dan akuntabilitas. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan deskriptif. Responden penelitian ini terdiri dari sekretaris desa, bendahara PKK, dan perwakilan masyarakat. Teknik pengumpulan data adalah dengan wawancara, observasi dan dokumentasi. Teknik analisis data dimulai dengan pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa aparatur Desa Pusaka Rakyat, Kecamatan Tarumajaya telah menerapkan prinsip transparansi dan akuntabilitas dalam pengelolaan APBDes. Perencanaan dan implementasi APBDes telah menerapkan prinsip transparansi dan akuntabilitas. Sementara akuntabilitas APBDes secara fisik menunjukkan implementasi yang akuntabel. Kendala utama adalah pencairan sumber pendanaan yang tidak sesuai dengan rencana. Kata Kunci : Akuntabilitas , APBDes